Lettering, Neville House - Ghosh, Ayan (2023)
Neville House is owned by the Wadia Group and named after its former chairman, Neville Wadia (1911-1996). In 1952, he succeeded his father Ness Wadia as chairman of Bombay Dyeing, which started in 1879. Under Neville Wadia's leadership, Bombay Dyeing became one of India's largest textile producers and one of its most recognizable consumer brands.